Indications for papillotomy according to new pathophysiological acquisitions of the choledochopancreaticoduodenal confuent - Cosco Montaldo, Homero (Cirugía del Uruguay, 2020)
Comparing surgical experience with the data obtained from dne-radiography, seriography and electromanometric recordings, the location of the ampulla of Vater is set in the submucous segment of the oddian canal. Two types of calculus of the oddian canal are described: that of the ampulla and the mural calculus, with their clinical, diagnostic and surgical differences. The difficulties of biliary catheterism are studied, with a description of three types of angulation of the oddian canal, and recommendation for its straightening by traction to ease the pasage of the catheter. For the extFaction of the calculus of the ampulla of Vater three maneuvres are recommended: retro duodeno pancreatic separation, controlled catheterism and supported biliary dredging, which, properly carried out, make for greater success in the upper or choledocotomy route and more exceptional the need for duodenopapillotomy.